Multicystic peritoneal mesothelioma treated with cytoreductive surgery followed or not by hyperthermic intraperitoneal chemotherapy: results from a large multicentric cohort. (1st January 2021) - Kepenekian, Vahan; Péron, Julien; Goéré, Diane; Sgarbura, Olivia; Delhorme, Jean-Baptiste; Eveno, Clarisse; Benzerdjeb, Nazim; Bonnefoy, Isabelle; Villeneuve, Laurent; Rousset, Pascal; Abboud, Karine; Pocard, Marc; et al.
Abstract: Background: Multicystic peritoneal mesothelioma (MCPM) is a rare, slowly growing, condition prone to recur after surgery. The role of hyperthermic intraperitoneal chemotherapy (HIPEC) added to complete cytoreductive surgery (CRS) remains controversial and difficult to assess. As patients are mostly reproductive age women, surgical approach, and fertility considerations are important aspects of the management. This observational retrospective review aimed to accurate treatment strategy reflections. Methods: The RENAPE database (French expert centers network) was analyzed over a 1999–2019 period. MCPM patients treated with CRS were included. A special focus on HIPEC, mini-invasive approach, and fertility considerations was performed. Results: Overall 60 patients (50 women) were included with a median PCI of 10 (4–14) allowing 97% of complete surgery, followed by HIPEC in 82% of patients. A quarter of patients had a laparoscopic approach. Twelve patients (20%) recurred with a 3-year recurrence free survival of 84.2% (95% confidence interval 74.7–95.0). The hazard of recurrence was numerically reduced among patients receiving HIPEC, however, not statistically significant (hazard ratio 0.41, 0.12–1.42, p  = 0.200). A severe post-operative adverse event occurred in 22% of patients with five patients submitted to a subsequent reoperation. Among four patients with a childbearing desire, three were successful (two had a laparoscopic-CRS-HIPEC and one a conventional CRS without HIPEC). Conclusion: MCPM patients treatment should aim at a complete CRS. The intraoperative treatment options as laparoscopic approach, fertility function sparing and HIPEC should be discussed in expert centers to propose the most appropriate strategy.